Analysis of mathematical communication skill of junior high school studentsin geometry topics based on early understanding of mathematics - A Rohmah; D Darhim; A Jupri (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The purpose of this study is to analyze the results of the test of students' mathematical communication skills on the topic of geometry. This research method is a qualitative research with the participants as many as 25 students in 8 grade of a junior high school in Bandung, then grouped based on early understanding of mathematics. Instrument used in this research are interview and written test with problem which presented refers to indicator of student's mathematical communication skill. The results showed that upper-level students were able to describe the answers correctly, not yet structured in the presentation of the answer, it therefore can cause the skill in using mathematical terms and the presentation of mathematical ideas are still weak. While middle-level students experienced barriers in describing relationships and situations models, and connecting real objects, images, and diagrams into mathematics. In addition, lower-level students have not been able to interpret the problems of communication in correct answers yet. The conclusion is that the mathematical communication skill of students is still lack. So that there needs appropriate learning strategy to improve student's mathematical communication skill.